Does Match Really Matter? The Moderating Role of Resources in the Relation between Demands, Vigor and Fatigue in Academic Life. Issue 6 (2nd May 2021) - de Jonge, Jan; Huter, Femke F.
Abstract: The goal of the present study is to examine the moderating role of resources at work or study in the relation between demands, vigor, and fatigue in academic life. Trying to replicate scarce research on both academic and student stress simultaneously, we tested the so-called triple-match principle in an academic context to study whether or not match between specific resources, demands and well-being/health outcomes does really matter. A cross-sectional survey study using online self-completion questionnaires was carried out among 96 academics and 221 engineering students from a technological university ( n = 317 in total). Findings showed a moderating, matching, role of resources in the association between demands, vigor, and particularly fatigue. Specifically, high cognitive resources strengthened the positive relation between cognitive demands and cognitive liveliness. In addition, high emotional resources buffered the positive association between emotional demands and successively emotional, cognitive and physical fatigue. This study reveals that matching resources are important in academic life. Therefore, it seems essential to create an appropriate equilibrium between specific resources and corresponding demands to promote academic well-being and health.